The Effect of Shinrin Yoku (Forest Bathing) Concept on Decreasing Academic Stress of College Students: A Pre-Experimental Study - Mustika, Shinta; Gamayanti, Witrin; Kurniawati, Fitri; Jaenudin, Ujam (UI Scholars Hub, 2026)
Academic stress is a common issue among university students due to heavy academic demands and performance pressure, affecting both physical and mental well-being. This study examines the effectiveness of shinrin-yoku (forest bathing) in reducing academic stress. Using a quantitative pre-experimental one-group pretest-posttest design, stress levels were assessed before and after a session of shinrin-yoku among six Cianjur students with high academic stress. The research was conducted in locations within the scientific collection area of Cibodas Botanical Garden, identified as suitable for health and well-being interventions. The Profile of Mood States (Indonesian version) and Perception of Academic Stress Scale were used for measurement. Paired sample t-test analysis revealed a significant reduction in academic stress (p=0.03). Results indicate that shinrin-yoku effectively reduces academic stress by decreasing negative mood and enhancing positive mood. This study provides preliminary evidence that shinrin-yoku may be a nature-based approach to support students’ mental well-being, particularly in high-stress academic. However, the small sample size, pre-experimental design without a control group, and single-session intervention limit the generalizability and long-term interpretation of the findings.